Intravoxel incoherent motion (IVIM) MR imaging of colorectal liver metastases: Are we only looking at tumor necrosis?. Issue 2 (30th May 2013) - Chiaradia, Melanie; Baranes, Laurence; Van, Jeanne Tran; Vignaud, Alexandre; Laurent, Alexis; Decaens, Thomas; Charles‐Nelson, Anaïs; Brugières, Pierre; Katsahian, Sandrine; Djabbari, Marjane; Deux, Jean‐François; Sobhani, Iradj; et al.
<x xml:space="preserve">Abstract</x> Purpose To determine if intra‐voxel incoherent motion diffusion‐weighted imaging (IVIM‐DWI) parameters, including free molecular‐based (D) and perfusion‐related (D*, f) diffusion parameters, correlate with the degree of tumor necrosis and viable tumor in colo‐rectal cancer (CRC) metastasis. Materials and Methods Fifteen patients referred for resection of liver metastases from CRC were retrospectively included in this Institutional Review Board approved study. An IVIM‐DWI sequence was performed on a 1.5 Tesla MR imaging system, with 10 b factors (0, 10, 20, 30, 50, 80, 100, 200, 400 and 800 s/mm2). Mean D, D*, f and apparent diffusion coefficient (ADC) values were determined in metastases with a longest diameter above 10 mm. Correlations between the diffusion parameters and the degree of liver tumor necrosis and viable tissue were determined (Spearman). Results Correlation between diffusion parameters and histopathological findings was performed in 35 hepatic metastases with a diameter of more than 10 mm (mean size of 17.9 mm; range, 1–68 mm). Both D (r = 0.36; P = 0.035) and ADC (r = 0.4; P = 0.02) correlated with the degree of tumor necrosis but not with viable tumor. Conclusion ADC variation observed in CRC metastases following systemic chemotherapy reflects a specific increase in free‐molecular diffusion (D), in itself correlated to the degree of metastasis necrosis. J. Magn. Reson. Imaging 2014;39:317–325. © 2013 Wiley Periodicals, Inc.